PENGARUH PENUNDAAN PERONTOKAN DAN WAKTU PENGERINGAN TERHADAP MUTU FISIK BERAS KULTIVAR MEKONGGA - Ilmi Rohman, Muhammad Bahrul; Budirokhman, Dodi; Saleh, Ismail (Agroswagati : Jurnal Agronomi, 2025)
Rice is the main staple food in Indonesia, and its quality is strongly influenced by post-harvest handling, particularly threshing and drying practices. Mekongga cultivar is one of the widely cultivated high-yield rice varieties, but its grain quality can decline when threshing and drying are delayed. This study aimed to determine the effect of delayed threshing and drying duration on the physical quality of Mekongga rice. The research was conducted in Bugistua Village, Indramayu, from April to July 2022 using a factorial randomized complete design (RCD) with two factors: delay in threshing (1, 3, and 6 days) and drying duration (1, 2, and 3 days). Each treatment was replicated three times, resulting in 27 experimental units. Observations were made on grain moisture content, percentage of yellow grains, head rice, broken rice, and milling recovery. Statistical analysis was performed using analysis of variance (ANOVA) followed by Duncan’s multiple range test at a 5% significance level. The results showed that delayed threshing and drying duration independently affected some quality parameters, while interaction effects were observed on grain moisture content after drying. A one-day threshing delay combined with one to two days of drying resulted in lower moisture content and better rice quality compared to longer delays. Extended delays of six days increased yellow grain percentage and reduced milling recovery, indicating quality deterioration. In conclusion, immediate threshing or a maximum delay of one day, followed by two days of drying, is recommended to maintain optimal physical quality of Mekongga rice.